Sense of coherence in young adults: an integrative review - Álvarez-Rodriguez, Mackarena (Universidad de Sonora, 2023)
Introduction: The salutogenic theory presents a different approach for the study of health, which is the movement that takes towards the extreme ends in the line of the well-being-discomfort continuum. This theory has two key concepts: sense of consistency and general resources of resistance. The sense of coherence is considered useful in coping and in adapting to the special needs of the different stages of life. Objective:  Identify the role of sense of coherence and influencing factors in young adults. Methodology: Revisão integrativa, com metodologia de 6 etapas, segundo Botelho, Cunha, Macedo, a busca de artigos foi realizada nas bases de dados WOS, SCOPUS, PubMed e SciELO, durante o mês de julho de 2020, utilizando os descritores Sense of coherence OR Salutogenesis AND Young adult. Of the 1161 potential articles found, 11 were selected. Results: A strong sense of coherence was evidenced in young adults, which was influenced by culture, sex, educational level, economic income, and social support. Conclusion: The sense of coherence has a protective role in young adults, given the fact that it reduces the impact of stressful events. The evidence analyzed regarding the associated factors is not conclusive, therefore, further studies with methodological rigor are required.